Revealing the mechanism of lymphoid and myeloid cell differentiation and transdifferentiation through landscape quantification - Chenyong Zhang; Chunhe Li (Physical Review Research, 2021)
The hematopoietic stem cells (HSCs) can differentiate to myeloid and lymphoid lineages, which lead to more specific differentiated cells. This cell fate decision process is governed by an underlying gene regulatory network. However, its underlying mechanism remains to be fully clarified. In this work, based on a gene regulatory network of HSC differentiation, we built a dynamical model and developed an optimization approach to infer model parameters by fitting experimental data quantitatively. We mapped out the potential landscape of HSC differentiation and identified multistable cell states observed in experiments, including multipotent progenitor, B-cell, and macrophage. Interestingly, we also identified one new intermediate cell state on the landscape, which plays a critical role on the cellular transdifferentiation. By calculating the transition action among different attractor states, we quantified kinetic transition paths for differentiation and transdifferentiation between different cell states and identified key genes and regulations during these transition processes. Our work provides a general approach to construct a gene regulatory network model based on experimental data and new insights into the roles of intermediate states on the transdifferentiation process in HSC development.